The Use of Building Information Modeling (BIM) by Studying Building Orientation in Design to Reach more Sustainable Buildings - وسوف مصطفى; عمران جمال (Latakia University Journal -Engineering Sciences Series, 2023)
Energy is one of the most important issues that attract the attention of the whole world, although interest in it is still very limited. This, in turn, is reflected in the increase in energy consumption. This increase comes primarily in residential and industrial buildings by opening windows and doors. The walls of buildings with poor insulation also cause energy loss, so the process of evaluating the efficiency and quality of internal spaces is an important step from which the process of developing these spaces and upgrading them to reach sustainable models in terms of environmental, economic and social terms. The research aims to study the distribution modes of residential exchanges and their reflection on energy for a residential suburb consisting of twenty blocks in Tartous Governorate, through the development of a software tool using the Dynamo, which is one of the methods of visual programming, which is one of the latest tools currently used in BIM technology with the use of the Python programming language This tool studies the formed shadows and their effect on the neighboring buildings every hour of the year in order to know the area of ​​the facades that are exposed to the lovely winter sun, which in turn improves the thermal comfort of users, in addition to studying the heating and air conditioning loads for the current situation of orientation and comparing them with the loads after guiding the building at different angles In order to reduce consumption and benefit from solar radiation sources by Revit, which is classified among the most important BIM software, in addition to proposing a tool to achieve the building envelope at the design stage, since most of the energy leaking that increases the heat load is due to the external walls, floors adjacent to the soil, ceilings and windows in order to achieve the design requirements of the Syrian thermal insulation code using Dynamo and the Python language in order to reach sustainable, energy-saving buildings that benefit from sunlight and reduce the consumption of fossil energy